Survival in patients with malignant pleural effusion undergoing talc pleurodesis. (November 2019) - Hassan, Maged; Mercer, Rachel M; Maskell, Nick A; Asciak, Rachelle; McCracken, David J; Bedawi, Eihab O; Shaarawy, Hany; El-Ganady, Anwar; Psallidas, Ioannis; Miller, Robert F; Rahman, Najib M
Highlights: Successful pleurodesis is associated with survival benefit in malignant effusion. The survival benefit is maintained after controlling for primary tumour type. Talc pleurodesis success rates vary between 50–80% according to setting. Abstract: Objectives: Recent observations indicate a potential survival benefit in patients with malignant pleural effusion (MPE) who achieve successful pleurodesis in comparison to patients who experience effusion recurrence post pleurodesis. This study aimed to explore this observation using two datasets of patients with MPE undergoing talc pleurodesis. Materials and Methods: Dataset 1 comprised patients who underwent talc pleurodesis at Oxford Pleural Unit for MPE. Dataset 2 comprised patients enrolled in the TIME1 clinical trial. Pleurodesis success was defined as absence of need for further therapeutic procedures for MPE in the three months following pleurodesis. Data on various clinical, laboratory and radiological parameters were collected and survival was compared according to pleurodesis outcome (success vs. failure) after adjusting for the aforementioned parameters. Results: Dataset 1 comprised 60 patients with mean age 74.1±10.3 years. The most common primary malignancies were mesothelioma, breast and lung cancer. 29 patients (48.3%) achieved pleurodesis. The adjusted odds ratio (aOR) for poor survival with pleurodesis failure was 2.85 (95% CI 1.08–7.50, =p 0.034). Dataset 2 comprised 259 patients from the TIME1 trial. The mean age was 70.8±10.3 and the most common primary malignancies were mesothelioma, lung and breast cancer. Pleurodesis was successful in 205 patients (79%). aOR for poor survival was 1.62 (95% CI 1.09–2.39, p = 0.015). Conclusion: Achieving pleurodesis seems to impart a survival benefit in patients with MPE. Further studies are required to explore factors that may contribute to this phenomenon and to address the difference in survival between pleurodesis and indwelling pleural catheter interventions.